2019
DOI: 10.1016/j.corsci.2019.03.037
|View full text |Cite
|
Sign up to set email alerts
|

STEM-EELS identification of TiOXNY, TiN, Ti2N and O, N dissolution in the Ti2642S alloy oxidized in synthetic air at 650 °C

Abstract: Oxide-alloy interface of Ti6242S Ti-based alloy was investigated by STEM-EELS technique, after oxidation in both N 2-free and synthetic air atmospheres at 650°C for 1000 h. The chemical shift of Ti-L 2,3 edge and its specific fine structure along the oxide-alloy interface were used as fingerprint to distinguish the different compositions of titanium nitrides and oxynitrides. TiN, Ti 2 N and TiN x O y were identified in the sample oxidized in synthetic air at the oxide-alloy interface. Moreover, a decreasing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 25 publications
6
36
1
Order By: Relevance
“…However, the Al depletion, due to oxide scale growth and interdiffusion with the substrate alloy, leads to a nearly linear oxidation kinetics upon further exposure. After the cyclic oxidation test the oxide scale is composed of a mixture of titania and alumina, with formation of Ti and Ti-Al nitrides at the metal-scale interface, which is similar to the investigated uncoated TiAl and other alloys of this type [14,43,53].…”
Section: Discussionmentioning
confidence: 71%
“…However, the Al depletion, due to oxide scale growth and interdiffusion with the substrate alloy, leads to a nearly linear oxidation kinetics upon further exposure. After the cyclic oxidation test the oxide scale is composed of a mixture of titania and alumina, with formation of Ti and Ti-Al nitrides at the metal-scale interface, which is similar to the investigated uncoated TiAl and other alloys of this type [14,43,53].…”
Section: Discussionmentioning
confidence: 71%
“…11c), Ti-L 2,3 edges are compared with a previous study on Ti-6Al-2Sn-4Zr-2Mo-Si oxidised in synthetic air, where a rutile TiO 2 scale grew on the alloy and was identified by EELS and SAED techniques [37]. The comparison of Ti-L 2,3 ELNES fine structure of spectrum 8 with the work of Abdallah et al [37] revealed that the oxide has an anatase structure due to a difference in shape and to a change in position to slightly lower energy loss value of 'b' peak [40].…”
Section: Region 1: Intragranular Oxidation Areamentioning
confidence: 94%
“…In 3d transition metals, such as Ti, ELNES spectra are identified by L 3 and L 2 white lines that represent the spinorbit splitting of 2p core hole and transition to 3d states (L 3 from 2p 3/2 → 3d and L 2 from 2p 1/2 → 3d) [34,35]. Metallic Ti-L 3 and L 2 white lines are usually detected at 457 and 462.5 eV [36,37]. Ti bonding with O to form oxides, leads to a split in the L 2 and L 3 white lines and four peaks are detected instead of two.…”
Section: Region 1: Intragranular Oxidation Areamentioning
confidence: 99%
“…2i-o. The presence of a titanium nitrides (TiN or Ti 3 N) layer below the oxide scale has already been observed after the oxidation of Ti6242S (35)(36)(37). Atom probe tomography characterization of oxidized 62425 at 650 °C in air for 1000 h revealed the presence of a layer of Ti-oxynitride and, below it, a layer of TizN (with 35 at%N) enriched in Sn, Zr and Si and deple ted in Al (37).…”
Section: Resultsmentioning
confidence: 99%